Enhancing Charge Separation through Oxygen Vacancy‐Mediated Reverse Regulation Strategy Using Porphyrins as Model Molecules. Issue 40 (15th September 2020) - Yin, Dan; Ning, Xingming; Zhang, Ruizhong; Du, Peiyao; Zhang, Dongxu; Deng, Yang; Liu, Jia; Zhang, Qi; Zhang, Zhen; Lu, Xiaoquan
Abstract: Highly efficient charge separation has been demonstrated as one of the most significant steps playing decisive roles in enhancing the overall efficiency of photoelectrochemical (PEC) processes. In this study, by employing 5, 10, 15, 20‐tetrakis (4‐carboxyphenyl) porphyrin‐Ni (NiTCPP) as a prototype, an oxygen vacancy (Vo)‐mediated reverse regulation strategy is proposed for tuning hole transfer, which in turn can accelerate the transport of electrons and thus enhancing charge separation. The optimal NiO/NiTCPP system exhibits much higher (≈40 times) photocurrent and longer (≈13 times) lifetime of charge carriers compared with those of pure NiTCPP. Furthermore, the electron transfer kinetic rate constant ( K eff ) is quantitatively determined by an efficient scanning photoelectrochemical microscopy (SPECM). The K eff of the optimal system has a 5.7‐fold improvement. In addition, the similar enhancement in charge separation from other semiconductors (CoTCPP and FeTCPP) are also observed, indicating that the Vo‐mediated reverse regulation strategy is a promising pathway for tuning the properties of light harvesters in solar energy conversion. Abstract : An efficient oxygen vacancy (VO )‐mediated reverse regulation strategy is proposed to enhance charge separation using porphyrin (NiTCPP) as a prototype and coupled with semiconductor NiO. By regulating the concentration of VO in NiO, the hole transfer can be tuned, which in turn could accelerate the transport of electrons and thus enhancing charge separation.